Fluid shear stress-modulated chromatin accessibility reveals the mechano-dependency of endothelial SMAD1/5-mediated gene transcription - Jerome Jatzlau; Paul-Lennard Mendez; Aybuge Altay; Lion Raaz; Yufei Zhang; Sophia Mähr; Akin Sesver; Maria Reichenbach; Stefan Mundlos; Martin Vingron; Petra Knaus (iScience, 2023)
Summary: Bone morphogenetic protein (BMP) signaling and fluid shear stress (FSS) mediate complementary functions in vascular homeostasis and disease development. It remains to be shown whether altered chromatin accessibility downstream of BMP and FSS offers a crosstalk level to explain changes in SMAD-dependent transcription. Here, we employed ATAC-seq to analyze arterial endothelial cells stimulated with BMP9 and/or FSS. We found that BMP9-sensitive regions harbor non-palindromic GC-rich SMAD-binding elements (GGCTCC) and 69.7% of these regions become BMP-insensitive in the presence of FSS. While GATA and KLF transcription factor (TF) motifs are unique to BMP9- and FSS-sensitive regions, respectively, SOX motifs are common to both. Finally, we show that both SOX(13/18) and GATA(2/3/6) family members are directly upregulated by SMAD1/5. These findings highlight the mechano-dependency of SMAD-signaling by a sequential mechanism of first elevated pioneer TF expression, allowing subsequent chromatin opening to eventually providing accessibility to novel SMAD binding sites.